Guidelines on the intraoperative transfusion of red blood cells: a protocol for systematic review. Issue 6 (17th June 2019) - Baker, Laura; Park, Lily; Gilbert, Richard; Martel, Andre; Ahn, Hilalion; Davies, Alexandra; McIsaac, Daniel I; Saidenberg, Elianna; Tinmouth, Alan; Fergusson, Dean A; Martel, Guillaume
Abstract : Introduction: A significant proportion of red blood cell (RBC) transfusions are administered intraoperatively; yet there is limited evidence to guide transfusion decisions in this setting. The objective of this systematic review is to explore the availability, quality and content of clinical practice guidelines (CPGs) reporting on the indication for allogenic RBC transfusion during surgery. Methods: Major electronic databases (MEDLINE, EMBASE and CINAHL), guideline clearinghouses and Google Scholar, will be systematically searched from inception to January 2019 for CPGs pertaining to indications for intraoperative allogenic RBC transfusion. Characteristics of eligible guidelines will be reported in a summary table. The AGREE II instrument will be used to appraise the quality of identified guidelines. Recommendations advising on indications for intraoperative RBC transfusion will be manually extracted and presented to allow for comparison of similarities and/or discrepancies in the literature. Ethics and dissemination: The results of this systematic review will be disseminated through relevant conferences and peer-reviewed journals. Trial registration number: CRD42018111487